2020
DOI: 10.1007/s40152-020-00166-2
|View full text |Cite
|
Sign up to set email alerts
|

South Africa’s port doctrine: dilemmas and the way forward

Abstract: This study uses content analyses to examine 137 stakeholders' submissions to the Ports Regulator of South Africa from 2009/ 2010 to 2018/2019, classifying themes into two broad categories, namely port authority pricing and port governance, which together define South Africa's port doctrine. Results show that South Africa's system of eight commercial seaports is unique and is financed and managed using a mix of elements from the Anglo-Saxon and Asian doctrines and attempts to charge port tariffs according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Hence, there may be cross-subsidisation between ports and port users and a sharing of resources between the nine ports. The NPA also controls the licensing of terminal operators, and this has been an issue with some stakeholders that believe there are competition issues and a conflict of interest as the NPA, under Transnet, issues licenses to both private sector terminals and their sister division called Transnet Port Terminals (TPT) (Meyiwa & Chasomeris 2020). Consequently, the NPA makes a single annual tariff submission to the Ports Regulator, using the RR model to calculate the RR for the entire NPA.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, there may be cross-subsidisation between ports and port users and a sharing of resources between the nine ports. The NPA also controls the licensing of terminal operators, and this has been an issue with some stakeholders that believe there are competition issues and a conflict of interest as the NPA, under Transnet, issues licenses to both private sector terminals and their sister division called Transnet Port Terminals (TPT) (Meyiwa & Chasomeris 2020). Consequently, the NPA makes a single annual tariff submission to the Ports Regulator, using the RR model to calculate the RR for the entire NPA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A complex structure with the NPA as a regulated division of an unregulated group, together with consolidated accounting techniques, results in unnecessary complexity and inadequate access to information that could improve port regulation. Indeed, a study by Meyiwa and Chasomeris (2020) used content analyses to examine 137 port stakeholders' submissions from 2009/2010 to 2018/2019. They concluded that the governance structure of the NPA was shown to promote anticompetitive behaviour and they recommend a swift incorporation of the NPA as a stand-alone entity outside of Transnet.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Improved performance and competitiveness of ports are also part of stakeholder challenges, which require a configuration aimed at responding to the external operating environment, strategies, and structures of the port organization. Moreover, the challenges are how to assess the impact of reforms, achieve systemic coordination within complex port systems, and implement market-oriented strategies [50][51][52][53][54].…”
Section: Effects Of Competition and Cooperation On Port Governancementioning
confidence: 99%